Rawapening Lake Buffer Zone Management - Kalmah, Kalmah; Larasati, Endang; Purnaweni, Hartuti; Kismartini, Kismartini (Jurnal Teknik Sipil dan Perencanaan, 2022)
Abstract. Rawapening Lake is located in Semarang District, Central Java. The decreasing of Rawapening lake function due to its many problems caused by environmental degradation which has happened for almost three decades.  Buffer zone determination is a very important basic action to safe Rawapening Lake. This research is to determine Rawapening lake buffer zone and its management. Hydraulic, topographic analysis was conducted within the research along with identification of buffer zone condition. A clear buffer zone area act as boundary for Rawapening lake utilization to support the sustainability of its function in the future.